Investigation on morphological and molecular fingerprints of penguin brain using label-free optical imaging and spectroscopic techniques - Bhatt, Sunil; Verma, Ashwani Kumar; Dastidar, Prabir G.; Kumar, Punit; Thapa, Pramila; Jacob, Tony George; Roy, Tara Sankar; Iyengar, Soumya; Kumaran, Senthil; Ahluwalia, Balpreet Singh; Mehta, Dalip Singh (Scientific Reports, 2025)
The morphology and molecular study of the penguin brain are crucial to define its survival in the extreme conditions of Antarctica. The present study focusses on extracting different optical parameters of the penguin brain using label-free optical imaging and spectroscopic techniques. In label-free optical imaging, we have used quantitative phase imaging, which provides morphological information about the neurons in brain tissue, giving the quantitative phase value of 5 to 20 radians corresponding to the 8 µm tissue section. In label-free spectroscopic techniques, we have used autofluorescence and Raman spectroscopy. Autofluorescence spectroscopy provides molecular information about nicotinamide dinucleotide, flavins, lipofuscins, and porphyrins in the brain’s spectral range of 420 nm to 700 nm. Raman spectroscopy provides multiple peaks associated with different molecules in the brain; among them, few signals are observed at approximately 1305 cm−1, 1448 cm−1, and 1661 cm−1, which correspond to vibrational modes indicative of vibrational features within lipids and protein structures, as well as the presence of amide groups within brain tissue constituents. All these techniques provide the microscopic and molecular fingerprint of the penguin brain, which can be useful for understanding penguin’s anatomical, physiological, and social behavior.
Keywords: Antarktis; anatomi; biofysikk; biologi; biomarkører; fysiologi; morfologi; nevrologi; pingviner

Response of Antarctic sea-ice algae to an experimental decrease in pH: a preliminary analysis from chlorophyll fluorescence imaging of melting ice - Castrisios, Katerina; Martin, Andrew; Müller, Marius N; Kennedy, Fraser; McMinn, Andrew; Ryan, Ken G (Polar Research, 2018)
Microorganisms confined to annual sea ice in the Southern Ocean are exposed to highly variable oxygen and carbonate chemistry dynamics because of the seasonal increase in biomass and limited exchange with the underlying water column. For sea-ice algae, physiological stress is likely to be exacerbated when the ice melts; however, variation in carbonate speciation has rarely been monitored during this important state-transition. Using pulse amplitude modulated fluorometry (Imaging-PAM, Walz), we documented in situ changes in the maximum quantum yield of photosystem II ( F v / F m ) of sea-ice algae melting out into seawater with initial pH values ranging from 7.66 to 6.39. Although the process of ice-melt elevated seawater pH by 0.2–0.55 units, we observed a decrease in F v / F m between 0.02 and 0.06 for each unit drop in pH during real-time fluorescence imaging. These results are considered preliminary but provide context for including carbonate chemistry monitoring in the design of future sea ice state-transition experiments. Imaging-PAM is a reliable technology for determining F v / F m , but is of limited use for obtaining additional photosynthetic parameters when imaging melting ice.
Keywords: Sørishavet; alger; fotosyntese; fysiologi; havis; karbonatkjemi; marin biologi; sjøis; økofysiologi

Adjustment of pigment composition in Desmarestia (Desmarestiaceae) species along a sub-Antarctic to Antarctic latitudinal gradient - Mansilla, Andrés; Méndez, Fabio; Murcia, Silvia; Rodriguez, Juan Pablo; Marambio, Johanna; Rosenfeld, Sebastián; Yokoya, Nair; Bischof, Kai (Polar Research, 2016)
Photosynthesis at high latitudes demands efficient strategies of light utilization to maintain algal fitness and performance. The fitness, and physiological adaptation, of a plant or algae species depends in part on the abundance and efficiency of the pigments it can produce to utilize the light resource from its environment. We quantified pigment composition and concentration in six species of the brown macroalgal genus Desmarestia, collected from sub-Antarctic sites (Strait of Magellan, Beagle Channel–Cape Horn Province) and sites on the Antarctic Peninsula and adjacent islands. Sub-Antarctic Desmarestia species exhibited lower concentrations of chlorophyll a, chlorophyll c and fucoxanthin than endemic Antarctic species. Antarctic samples of D. menziesii and D. antarctica collected along a decreasing latitudinal gradient showed spatial and interspecific differences in light-harvesting pigment composition. Our results suggest distinct physiological adjustments in Desmarestia species in response to heterogeneous abiotic environmental conditions. The marine sub-Antarctic and Antarctic ecosystems are characterized by harsh environments (e.g., extreme irradiance, photoperiod, temperature, salinity) to which the physiology of macroalgal species must adapt. Keywords: Macroalgae; Phaeophyceae; photosynthesis; physiology; environmental heterogeneity; Chile.
Keywords: Antarktis; alger; fotosyntese; fysiologi; planter

Haematological values of three Antarctic penguins: gentoo (Pygoscelis papua), Adélie (P. adeliae) and chinstrap (P. antarcticus) - Ibañez, Andrés E; Najle, Roberto; Larsen, Karen; Pari, Marcela; Figueroa, Amalia; Montalti, Diego (Polar Research, 2015)
It is established that haematological and biochemical parameters provide important data to assess the physiological condition and health status of wild birds. To undertake conservation physiology or ecophysiology work, it is therefore essential to establish baseline physiological parameters and how these parameters change with age and life history events. In this work, we determined and compared baseline haematology and serum biochemistry between adults and chicks of three Antarctic penguin species of the genus Pygoscelis: gentoo (P. papua), Adélie (P. adeliae) and chinstrap (P. antarcticus). Differences in adults among species were observed in haemoglobin and biochemical parameters such as total proteins, glucose and alkaline phosphatase activity. In addition, differences between adults and chicks in haematocrit, haemoglobin, total proteins and glucose concentration were determined. Moreover, we evaluated the electrophoretic protein profiles between adults and chicks of the genus Pygoscelis, and a conserved protein pattern was observed among species and ages in the genus. Altogether, the results suggest that biochemical and haematological differences among pygoscelids may be related to the nutritional status and energetic expenditure during breeding as well as their feeding habits and development stage. Keywords: Antarctic; haematology; physiology; Pygoscelis; penguins; serum biochemistry.
Keywords: Antarktis; biokjemi; biologi; fysiologi; hematologi; pingviner; zoologi

Adaptations and lifestyle in polar marine environments: a biological challenge for the study of fish evolution - Verde, Cinzia; Cocca, Ennio; de Pascale, Donatella; Parisi, Elio; di Frisco, Guido (Polar Research, 2004)
The climatic features of Antarctic waters are more extreme and constant than in the Arctic. The Antarctic has been isolated and cold longer than the Arctic. The polar ichthyofaunas differ in age, endemism, taxonomy, zoogeographic distinctiveness and physiological tolerance to environmental parameters. The Arctic is the connection between the Antarctic and the temperate-tropical systems. Paradigmatic comparisons of the pathways of adaptive evolution of fish from both poles address the oxygen-transport system and the antifreezes of northern and southern species, (i) Haemoglobin evolution has included adaptations at the biochemical, physiological and molecular levels. Within the study of the molecular bases offish cold adaptation, and taking advantage of the information on haemoglobin amino acid sequence, we analysed the evolutionary history of the ? and ? globins of Antarctic, Arctic and temperate haemoglobins as a basis for reconstructing phylogenetic relationships. In the trees, the constant physico-chemical conditions of the Antarctic waters are matched by clear grouping of globin sequences, whereas the variability typical of the Arctic ecosystem corresponds to high sequence variation, reflected by scattered intermediate positions between the Antarctic and non-Antarctic clades. (ii) Antifreeze (glyco)proteins and peptides allow polar fish to survive at sub-zero temperatures. In Antarctic Notothenioidei the antifreeze gene evolved from a trypsinogen-like serine protease gene. In the Arctic polar cod the genome contains genes which encode nearly identical proteins, but have evolved from a different genomic locus–a case of convergent evolution.
Keywords: Sørishavet; biokjemi; biologi; evolusjon; fauna; fisker; fysiologi; klima; miljø; zoogeografi; økosystemer

Man in extreme environments - Brubakk, Alf O. (Aviation, space, and environmental medicine, 2000)
Humans have demonstrated the ability to live and work in many adverse environments. Many examples demonstrate that our understanding of humans ability to adapt to extreme environments is limited, but it is reasonable to assume that the main problems in space exploration will be psychological and social. It is argued that polar expeditions of an earlier age are a better model for space exploration than confinement studies or Antarctic overwintering. Some aspects of the reason for the success of these expeditions are discussed and the lessons that can be used are pointed out.
Keywords: Antarktis; fysiologi; overvintring; polarekspedisjoner; polarområdene

Immune responses during an antarctic summer - Lugg, Desmond J.; Ursin, Holger; Donovan, Kevin; Konrad Muller, H.; Quinn, Dennis (Pathology, 1995)
The immune status of 29 members of the Australian National Antarctic Research Expeditions (ANARE) was investigated before, during, and after a 56 day summer voyage to Antarctica and correlated with psychological and physiological parameters. All subjects were healthy. Expedition personnel demonstrated decreased cell mediated immune responses (CMI) assessed by the CMI Multi-test; 21% were hypoergic. The major associated observation was a significant negative correlation with anxiety in Antarctica. However, perceived anxiety was greater before and after the voyage. No significant changes were found in T and B lymphocyte subsets, immunoglobulin and complement components and cutaneous blood flow, nor was there any clinical evidence of illness. Of the hormones examined only cortisol was low predeparture which may reflect increased perceived anxiety at that time. Changes in immune control mechanism were apparent as shown by reduced CMI responses and lowered tetanus antibody levels. Stress factors are postulated to induce depression of the immune response in Antarctica. The association with anxiety suggests that brain peptides or associated cytokines may have a role in mediating these immune events. Such alterations in immune status have implications for health management in isolated and extreme conditions.
Keywords: Antarktis; fysiologi; immunologi; psykologi

Light and productivity of phytoplankton in polar marine ecosystems: a physiological view - Sakshaug, Egil; Slagstad, Dag (Polar Research, 1991)
Keywords: Sørishavet; fysiologi; fytoplankton; planteplankton; polarområdene

Psychobiological Studies of Individuals in Small, Isolated Groups in the Antarctic and in Space Analogues - Ursin, Holger; Bergan, Tom; Collet, Jérôme; Endresen, Inger M.; Lugg, Desmond; Maki, Pauline; Matre, Roald; Molvær, Otto Inge; Müller, Helmut K.; Olff, Miranda; Pettersen, Roger C.; Sandal, Gro Mjeldheim; et al. (Environment and Behavior, 1991)
Mental and physical health are both at risk under conditions of prolonged remoteness from home and removal from normal social support networks. This article examines relevant data from small groups isolated in (a) Antarctic summer stations, (b) a Transantarctic traverse expedition, and (c) a spacecraft simulator capsule.
Keywords: Antarktis; forskningsstasjoner; fysiologi; immunologi; psykobiologi; psykologi

An Antarctic crossing as an analogue for long-term manned spaceflight - Ursin, Holger; Collet, Jérôme; Etienne, Jean L. (ESA Bulletin, 1990)
The long-duration space missions planned for the end of this century will involve both physiological and psychological problems for the crew who will fly them. If Europe is to achieve autonomy in space, it must increase its expertise in these associated disciplines. One means of acquiring relevant experience is to study human behaviour in environments that are similar from a psychological viewpoint. A planned crossing of the Antarctic by a six-man international team therefore offered ESA a unique opportunity to observe the psychological problems that can occur during an international expedition involving prolonged isolation in a hostile environment.
Keywords: Antarktis; fysiologi; psykologi

Thermal and metabolic responses of men in the Antarctic to a standard cold stress - Milan, Frederick A; Elsner, Robert W; Rodahl, Kaare (Journal of Applied Physiology, 1961)
Thermal and metabolic responses of eight male subjects exposed nude for 2 hr to a standard cold stress (17 α 1.0 C air temperature) were examined in the austral fall, winter, and spring at Little America in the Antarctic. Mean body, average skin and foot temperatures increased significantly after 3 months. Neither rectal nor finger temperatures were changed over the year. Although basal metabolic rates were unchanged, there was a significant decrease in the metabolic responses to the standard cold stress after 3 months in the Antarctic. It is suggested that these changes represent physiological adaptations to chronic cold. Submitted on November 14, 1960
Keywords: Antarktis; fysiologi; kuldeeksponering; kuldetoleranse; medisin

Changes in body-weight of men in the Antarctic - Wilson, Ove (British Journal of Nutrition, 1960)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fysiologi; observasjoner

Basal metabolic rate in the Antarctic - Wilson, Ove (Metabolism: Clinical and Experimental, 1956)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fysiologi; kuldetoleranse; medisin

Physiological changes in blood in the Antarctic. A preliminary report - Wilson, Ove (British Medical Journal, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskning; fysiologi; medisin; observasjoner